Telaah ‘urf tentang Tradisi Uang Japuik Perempuan kepada Laki-Laki: Studi Kasus pada Masyarakat Pariaman - Nurani, Gempita Refi; Hasan, Muhammad (VISA: Journal of Vision and Ideas, 2024)
The proposal that occurs in the standard is generally done by men to women and is different from what is in Pariaman, it is also found that japuik money, which occurs in Pariaman, where this tradition can also cause death as happened on November 18 where because of the amount of this japuik money, which is charged by the man to the woman's family to the man with a large amount of money and the entire event is borne by the woman's family. This causes this tradition to be questioned by maintaining it which can cause loss of life which is contrary to Islamic law and the teachings of humanity. In the era of society 5.0, which causes general welfare not to occur because of the preservation of this tradition. This study aims to explain the origin of japuik money which is customary in Pariaman. This research is a library research that uses an empirical approach, namely by tracing what happened in Pariaman, this study uses a qualitative method that uses books as the main data source, supported by articles, books, and books that are relevant to the research study. The explanation in this study is presented with analytical description. Based on the theory of 'urf, the tradition of money in Pariaman is contrary to religious teachings and positive law in Indonesia, although the practice is often carried out. From the findings of researchers, there are two opinions, if the tradition does not contradict the text of the hadith or the Qur'an, and the tradition is not burdensome, then the tradition is agreed to be maintained. If the tradition poses a danger of causing harm, then the tradition is less agreed to be maintained.